Concurrent Proteomic Fingerprinting and Molecular Analysis of Cyathostomins. Issue 7 (4th April 2019) - Bredtmann, Christina Maria; Krücken, Jürgen; Murugaiyan, Jayaseelan; Balard, Alice; Hofer, Heribert; Kuzmina, Tetiana A.; von Samson‐Himmelstjerna, Georg
Abstract: Rapid, cost‐effective, efficient, and reliable helminth species identification is of considerable importance to understand host–parasite interactions, clinical disease, and drug resistance. Cyathostomins (Nematoda: Strongylidae) are considered to be the most important equine parasites, yet research on this group is hampered by the large number of 50 morphologically differentiated species, their occurrence in mixed infections with often more than 10 species and the difficulties associated with conventional identification methods. Here, MALDI‐TOF MS, previously successfully applied to identify numerous organisms, is evaluated and compared with conventional and molecular genetic approaches. A simple and robust protocol for protein extraction and subsequent DNA isolation allowing molecular confirmation of proteomic findings is developed, showing that MALDI‐TOF MS can discriminate adult stages of the two closely related cyathostomin species Cylicostephanus longibursatus and Cylicostephanus minutus . Intraspecific variability of proteomic profiles within morphospecies demonstrated an identification of morphospecies with an accuracy of close to 100%. In contrast, three genospecies within C. minutus and sex‐specific profiles within both morphospecies could not be reliably discriminated using MALDI‐TOF MS. In conclusion, MALDI‐TOF MS complemented by the molecular protocol is a reliable and efficient approach for cyathostomin species identification.